The effect of immobilization in the PVA films on the fluorescence and phosphorescence lifetime of indole and its dervatives - Kowalska-Baron, Agnieszka; Choudhary, Preeti; Montes, Denise (Wydawnictwo Politechniki Łódzkiej, 2011)
This work is devoted to study how immobilization in the PVA films affects the fluorescence and phosphorescence lifetime of indole and its derivatives. The obtained results indicated that immobilization of the studied indoles in the PVA matrix, which leads to the increased microrigidity of the environment around the indole moiety, results in the increase of singlet and triplet excited state lifetime of the studied compounds. Most probably, the enhancement of the rigidity of the environment near the chromophore reduces the rates of the non-radiative deactivation pathways, which leads to the increase of excited state lifetimes of the studied compounds.